2021
DOI: 10.1002/ehf2.13661
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of people with heart failure in Australian general practice: results from a retrospective cohort study

Abstract: Aims Heart failure (HF) causes significant morbidity and mortality, but the rates and characteristics of people with HF in Australia are not well studied. SHAPE set out to describe the characteristics of HF patients seen in the real‐world setting. Methods We analysed anonymized patient data extracted from the clinical software of 43 participating GP clinics for the 5 year period from 1 July 2013 to 30 June 2018. Patients were stratified into ‘definite’ and ‘probable’ HF based on a hierarchy of selection criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Prevalence, clinical phenotype, and outcome About half of patients with HF has ID, [16][17][18] with specific prevalence estimates for ID in chronic HF ranging between 47 and 68% depending on the definition used for ID. 19 A slightly higher prevalence has been in general observed in HFpEF vs. HF with mildly reduced EF (HFmrEF) vs. HFrEF.…”
Section: Acute and Chronic Heart Failurementioning
confidence: 99%
“…Prevalence, clinical phenotype, and outcome About half of patients with HF has ID, [16][17][18] with specific prevalence estimates for ID in chronic HF ranging between 47 and 68% depending on the definition used for ID. 19 A slightly higher prevalence has been in general observed in HFpEF vs. HF with mildly reduced EF (HFmrEF) vs. HFrEF.…”
Section: Acute and Chronic Heart Failurementioning
confidence: 99%
“…26 In a large Australian primary care study of patients with heart failure, the prevalence of iron deficiency, defined in the same way, was 39.7%, and among people with self-reported heart failure in NHANES (National Health and Nutrition Examination Survey 2017-2018), the prevalence of iron deficiency was 48.2% (95% CI, 36.8%-59.7%). 27,28 A recent study from the United Kingdom reported an even higher prevalence, with 61% in patients with HFrEF iron-deficient. 29 Conversely, using an alternative definition based on sTFR, we found a much lower prevalence of iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…1 The most commonly recorded comorbidities were hypertension (41.1%), chronic obstructive pulmonary disease (COPD)/asthma (25.1%), depression/anxiety (18.4%), ischaemic heart disease (12.9%), diabetes (11.9%), osteoporosis (9.5%), renal impairment (4.0%) and atrial fibrillation (3.6%). 14 Patients with 'definite' or 'probable' HF attended their GP practice an average of 14.4 times per year (median 11.9), ranging from a mean of 11.7 (median 9.0) visits per annum for those with no recorded comorbidities to a mean of 27.2 (median 22.9) visits per annum for those with five or more comorbidities (Table 1).…”
Section: Resultsmentioning
confidence: 99%